Behavior of rat bone marrow stem cells on titanium surfaces modified by laser-beam and deposition of calcium phosphate - Florian, F. [UNESP]; Guastaldi, F. P.S. [UNESP]; Cominotte, M. A. [UNESP]; Pires, L. C. [UNESP]; Guastaldi, A. C. [UNESP]; Cirelli, J. A. [UNESP] (Springer Nature, 2021)
Objectives: The aim of this study was to evaluate the behavior of rat bone marrow stem cells seeded on a Ti-15Mo alloy surface modified by laser-beam irradiation followed by calcium phosphate deposition. Materials and methods: A total of four groups were evaluated: polished commercially pure titanium (cpTi): Ti-P; laser irradiation + calcium phosphate deposition on cpTi: Ti-LCP; polished Ti-15Mo alloy: Ti15Mo-P; and laser irradiation + calcium phosphate deposition on Ti-15Mo alloy: Ti15Mo-LCP. Before and after laser irradiation and calcium phosphate deposition on the surfaces, physicochemical and morphological analyses were performed: Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDX). The wettability of the samples was evaluated by contact angle measurement. In addition, the behavior of osteoblast-like cells to these surfaces was evaluated for cell morphology, adhesion, proliferation and viability, evaluation of alkaline phosphatase formation and gene expression of osteogenesis markers. Results: Surfaces wet-abrade with grit paper (P) showed oriented groves, while the laser irradiation and calcium phosphate deposition (LCP) produced porosity on both cpTi and Ti15Mo alloy groups with deposits of hydroxyapatite (HA) crystals (SEM). EDX showed no contamination after surface modification in both metal samples. A complete wetting was observed for both LCP groups, whereas P surfaces exhibited high degree of hydrophobicity. There was a statistical difference in the intragroup comparison of proliferation and viability (p < 0.05). The ALP activity showed higher values in the Ti15Mo alloy at 10 days of culture. The gene expression of bone related molecules did not present significant differences at 7 and 14 days among different metals and surface treatments. Conclusion: Ti15-Mo seems to be an alternative alloy to cpTi for dental implants. Surface treatment by laser irradiation followed by phosphate deposition seems to positively interact with bone cells. Clinical relevance: Ti-15Mo alloy surface modified by laser-beam irradiation followed by calcium phosphate deposition may improve and accelerate the osseointegration process of dental implants. [Figure not available: see fulltext.]